2015
DOI: 10.1007/s40265-015-0405-y
|View full text |Cite
|
Sign up to set email alerts
|

Use of Non-Vitamin K Antagonist Oral Anticoagulants in Special Patient Populations with Nonvalvular Atrial Fibrillation: A Review of the Literature and Application to Clinical Practice

Abstract: Atrial fibrillation is a commonly encountered arrhythmia associated with increased risk for thromboembolic events. Anticoagulation is necessary to decrease the risk of ischemic stroke. Traditionally, warfarin has been the only oral pharmacotherapeutic option for long-term anticoagulation in patients with nonvalvular atrial fibrillation (NVAF). Recently, non-vitamin K antagonist oral anticoagulants (NOAC), including dabigatran, rivaroxaban, apixaban, and edoxaban, have become available as alternatives for warfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 124 publications
0
3
0
1
Order By: Relevance
“…48,49 Moderate CYP3A4 inhibitors should be avoided in patients with renal impairment receiving rivaroxaban due to increased bleeding risk unless the benefit outweighs the potential risk. 48,50 Since aprepitant is a moderate inhibitor of CYP3A4, a theoretical interaction between aprepitant and rivaroxaban exists. Recommendations for apixaban are limited to strong CYP3A4 inhibitors only.…”
Section: Drug Interactions Between Aprepitant and Medications Metabolmentioning
confidence: 99%
“…48,49 Moderate CYP3A4 inhibitors should be avoided in patients with renal impairment receiving rivaroxaban due to increased bleeding risk unless the benefit outweighs the potential risk. 48,50 Since aprepitant is a moderate inhibitor of CYP3A4, a theoretical interaction between aprepitant and rivaroxaban exists. Recommendations for apixaban are limited to strong CYP3A4 inhibitors only.…”
Section: Drug Interactions Between Aprepitant and Medications Metabolmentioning
confidence: 99%
“…Дабигатран -прямой блокатор тромбина, введенный в клиническую практику для профилактики тромбоэмболических осложнений у больных с ФП, для неотложной терапии и вторичной профилактики тромбоза глубоких вен и тромбоэмболии легочной артерии, послеоперационной тромбопрофилактики и гепарин-индуцированной тромбоцитопении [19] В редких случаях дабигатран может вызвать тромбоцитопению (1% случаев), хотя основной механизм этого осложнения остается неясным [20]. Национальная база данных итальянского лекарственного агентства, содержащая все сообщения о побочных осложнениях дабигатрана, зафиксировала семь случаев развития тромбоцитопении.…”
Section: тромбоцитопения ассоциированная с приемом прямых пероральных...unclassified
“…Warfarin and other vitamin K antagonists were traditionally established as effective treatments, reducing the risk of stroke by about two-thirds [3]. In recent years, four non-vitamin K antagonist oral anticoagulants (NOACs) (apixaban, dabigatran, edoxaban, and rivaroxaban) have been introduced as replacements for warfarin in patients with AF; they reduce routine laboratory monitoring, have fewer drug and food interactions, and have a more rapid onset and offset of action compared with warfarin [4][5][6][7][8][9][10][11]. The body of evidence from clinical trials and meta-analyses has shown similar or superior efficacy of NOACs in stroke prevention compared with warfarin and an association with a similar or reduced risk of bleeding [4,6,[8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%